7th International Conference on Libraries (ICOL) 2025 “Towards Sustainable Future Libraries” - Ismail, Mohd Ikhwan (Perpustakaan Hamzah Sendut, Universiti Sains Malaysia, 2025)
The International Conference on Libraries (ICOL), organized by Universiti Sains Malaysia (USM) Library since 2005, will celebrate the 20th years anniversary in 2025 with its seventh edition. Scheduled on 23 - 24 September 2025, at Penang, Malaysia, the conference will focus on the theme "Towards Sustainable Future Libraries." Sustainable future libraries embracing practices, technologies, and strategies aimed at ensuring long-term environmental, social, and economic sustainability. Libraries are adopting eco-friendly designs and technologies, such as energy-efficient buildings, green certifications, and the use of renewable energy sources. Future libraries are leveraging emerging technologies, including artificial intelligence (AI), digitization, and cloud computing, to create more efficient and accessible services. It also prioritizes open access to information and resources, providing free or low-cost access to digital collections, research papers, and educational materials. ICOL 2025 will serve as a platform for information professionals from Malaysia and beyond to share knowledge, discuss trends, and explore developments in librarianship and information technology. It has grown to become one of the major events for information professionals in Malaysia. The program’s presentations are also applicable to public, academic, school, and special libraries’ interests.